Juridical Review of Criminal Acts of Mining Activities Outside the Mining Business Permit (WIUP) Area (Study Decision Number: 203/Pid.Sus/2023/PN.Bta) - Yasa, Mela; Ramasari, Risti Dwi; Nurina, Intan (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Transporting Mining Products without a permit is an activity that can be punished if you do not have a Document Permit or mining business permit (IUP) that is officially issued to a mining company, in accordance with Republic of Indonesia Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2020 2009 Concerning Mineral and Coal Mining. The Mining sector also has various challenges and debates related to environmental impacts, the rights of indigenous communities, and granting permits to Mining Companies. In Article 35 of Law no. 3 of 2020 explains that every mining business is required to have a business permit issued by the central government including business registration number, standard certificate and/or permits consisting of Mining Business Permit (IUP), Special Mining Business Permit (IUPK), Transport Services Business Permit ( IUJP), and Rock Mining Permit (SIPB) as a continuation of operations. Mining Business Permits (IUP) are mentioned in article 1 paragraph (7) of the Minerba Law. IUP consists of two stages of activities, namely exploration and production operations. Exploration must take priority before carrying out production operations. The problem is how to account for criminal acts of mining activities outside the mining business permit area in decision number: 203/Pid.Sus/2023/Pn.Bta and what are the judge's considerations in deciding cases of criminal acts of mining activities outside the mining business permit area in decision number: 203/Pid.Sus/2023/Pn.Bta. Legal research methods in this case are a science of how to conduct legal research in an orderly (systematic) manner. This research uses two approaches, namely the Normative Juridical and Empirical Juridical approaches. Secondary data is permitted through library research (Library Research) such as books, literature and scientific works related to research problems. Secondary data consists of 3 (three) legal materials, namely, primary, secondary and tertiary legal materials. Primary data can be obtained from the results of research in the field directly on the research object (Field Research) which is carried out through direct observation and interviews. Based on the research results obtained, it can be concluded that the defendant is legally and proven guilty of committing a criminal act and guilty of committing a criminal act of transporting coal that does not originate from the holder of a mining business permit (IUP), special mining business permit (IUPK), or permit as in the indictment. sole public prosecutor as regulated in article 161 of the Mineral and Coal Law which reads: every person who carries out mining without a permit shall be sentenced to imprisonment for a maximum of 5 years and a maximum of IDR. 100,000,000.00 (one hundred billion rupiah And thus the demands of the public prosecutor in decision number: 203/pid.sus/2023/PN.Bta with the defendant are lighter than the provisions of article 161 of the Mineral and Coal Law where the Public Prosecutor only demands that the defendant be 1 (one) year 3 months minus while the defendant was in detention with the order that the defendant remain detained and with Rp. 37,500,000,000 (thirty-seven billion five hundred million rupiah) subsidiary 1 (one) month. As well as the Judge's considerations in deciding the criminal act of mining activities outside the mining business permit area based on decision number: 203/pid.sus/2023/Pn.Bta The Panel of Judges decided and had a different opinion by only sentencing the defendant lighter than the Public Prosecutor's demand, namely 1 year 3 (three) months becomes imprisonment for 8 (eight) months and a fine of Rp. 37,500,000,000 (thirty-seven million five hundred million rupiah) provided that if the fine is not paid it will be replaced by imprisonment for 1 (one) month. The judge does not find anything that can eliminate criminal responsibility, either as a justification or excuse, so the defendant must be held accountable for his actions. The mitigating rights are that the defendant is polite in court, the defendant is frank and admits all the actions that the defendant committed, and the defendant is the breadwinner of the family and the defendant has never been convicted. To the public who wish to carry out activities related to and impacting the environment to be more careful and understand whether the activities carried out are criminal acts or not, for law enforcement by the Panel of Judges to be able to take more appropriate action regarding mining crimes outside the mining permit area so that they can cause harm. many parties and damage the environment, to the Panel of Judges to be more careful and thorough in deciding a case so that it is in accordance with the level of guilt of the defendant and the moral responsibility of the defendant, looking at the philosophical, sociological and juridical elements and the aggravating and mitigating factors, the Panel of Judges must provide The decision is considered to be very appropriate, so that the sentence imposed can fulfill a sense of justice for both the perpetrator and the State.